Pembiasaan Permainan Tradisional Banggai Kepulauan “Bois (Susun Balok)” di Sekolah Dasar sebagai Upaya Mengembangkan Kolaborasi dan Kebiasaan Berolahraga Anak Indonesia Hebat - Mayasari Mayasari; Nasta Nasta; Hasnita I. Labangsa; Aswandi Aswandi; Rosdianty S. Djahanab; Lia Nurhayati (Journal of Innovative and Creativity, 2025)
Traditional games are an important part of local culture, embodying social, moral, and educational values. Amidst the development of digital technology, traditional games are being abandoned by children. Yet, these activities have significant potential for character building and strengthening the dimensions of the Pancasila Student Profile. This article discusses the introduction of the traditional game Bois (Stacking Blocks), originating from the Banggai Islands, Central Sulawesi, as a medium for developing collaboration and sports habits in elementary school students. This game is played in groups using small blocks stacked by the players and a small paper ball thrown by the opponent. If a player is hit by the ball, they lose. Through this game, students learn to cooperate, communicate, practice sportsmanship, and cultivate active movement. The analysis shows that the introduction of the traditional game Bois is relevant to the dimensions of the Pancasila Student Profile, particularly collaboration and communication, and supports the habit of "Exercising" within the Merdeka Curriculum framework of the Great Indonesian Children.